Cytoprotective effects of honey in combination with aqueous and ethanol extracts from chromolaena odorata l. (Eupatorium Odoratum L.) in rats - Nur Jannah, M.H; Abdulla, Mahmood Ameen; Sidik, K.; Salmah, I. (Faculty of Medicine, University of Malaya, 2006)
Six groups of adult Sprague-Dawley rats were orally administered with a variety of treatments to elucidate their cytoprotective effects. Absolute ethanol combined with HCl was used to induce gastric lesions in rats. Aqueous and ethanol extracts of Chromolaena odorata, a famous folk herb for treating skin wounds were evaluated to determine their protective effect on gastric mucosa. In this study, aqueous extract and ethanol extract of C. odorata were combined with honey. In addition, honey alone and honey combined with cimetidine were also evaluated. Rat stomachs were examined grossly and histologically. Results were expressed as inhibition percentage. The honey and aqueous extract combination showed the highest inhibition percentage (72.67%) followed by honey and ethanol extract (58.92%), honey and cimetidine (56.55%) and the lowest was honey alone (46.74%). However, there were no significant differences between the effects of aqueous and ethanol extracts of C. odorata and honey in promoting cytoprotective effects and this may be due to the small sample size. Nevertheless, these results suggest that C. odorata and honey may be beneficial in treating induced gastric mucosal injury.